Combat Time in International Female Judo: A Systematic Review and Meta-Analysis - Aedo-Munoz, E (Idokan Poland Association, 2024)
Background. Rule changes in recent years might have interfered with the time spent in female judo combats. Furthermore, weight divisions may have different temporal combat behaviors and react differently to rule changes. Aim. To analyze data on combat time in international female judo between 2010–2019 by weight division. Methods. The following descriptors were searched in electronic databases (May 8 to June 11, 2021): (“technical-tactical” OR “time motion” OR “combat time”) AND (“judo” OR “combat sports” OR “martial arts”). 793 articles were found. After the screening process 6 were included in the systematic review and 5 in the meta-analysis. A total of 1, 485 combats were analyzed. The following information was extracted: mean and standard deviation of total combat time; frequency of combats finished in Regular time (RT) or Golden Score (GS); total combat time by weight division. Results. The combat time changed at each rule change and the year 2012 had the highest combat time (2012=260.9 seconds). The GS occurrence increased in 2018–2019 compared to 2013 (GS: 2013=4.4%; 2018–2019=18%; Z=2.87; p=0.004). The >78kg category had the highest GS occurrence in 2013 (16.7%) among all divisions. However, 5 out of 6 combats ended before RT in 2018–2019. The 48kg category maintained a low GS occurrence over the years. Conclusion. Combat times changed in the period 2010–2019, with a trend towards homogeneity by weight divisions in 2018–2019. However, the GS occurrence has increased over the years. © Yoshin Academy